تفسيرات المرأة لاضطراب علاقتها الجنسية الزوجية - دواجي بوعبد الله, ميلود (جامعة الوادي University of Eloued, 2018)
نظرا للواقع السوسيو ثقافي الذي تعيش في وسطه المرأة التي تعاني من اضطرابات نفسية وعقلية, وبخاصة ما تعلق منها باضطراب علاقتها الجنسية الزوجية، التي يعد التعبير عنها محظورا، لما تحمله من معتقدات وتصورات ثقافية قد ترجع أسباب الاضطراب إلى تفسيرات غير موضوعية ممثلة في تلبس الجني، وتأثير السحر على الصحة. لذلك فان دراستنا لهذا الموضوع، تهدف إلى معرفة أسباب الاضطراب، والمؤشرات التي تبنى عليها التفسيرات للمرض، ومدى علاقتها بالمسار العلاجي، كون هذه التفسيرات ما هي إلا إسقاطات لتصوراتها الثقافية في ضمن إطار العلاقة بين معاناتها النفسية وطبيعة التوجه العلاجي الذي يعكس طابع المحافظة على مكانتها داخل الجماعة التي تنتمي إليها، وبالتالي فان التوجه العلاجي يعكس فعلا جملة الاعتقادات التي تؤكد ما تحمله من مؤشرات على تحديد الإصابة المرضية. Due to the socio-cultural reality, a woman who is suffering from psychological and mental disorders, especially those related to her marital sexual disorder, It is forbidden to her to express her disease. In fact, because of cultural beliefs and perceptions, the causes of disorder may be attributed to non-objective interpretations like sorcery (witchcraft). Therefore, our study of this subject aims at identifying the causes of the disorder, the indicators on which the interpretations of the disease are based, and to what an extent they relate to the therapeutic course. The fact that these interpretations are only projections of their cultural perceptions within the framework of the relationship between psychological suffering and the nature of the therapeutic course, which reflects the character of maintaining its position within its belonging group. Therefore, the therapeutic approach reflects the beliefs that confirm the signs of the disease.
مقال
Keywords: العلاقة الجنسية، تصورات الاضطراب، المسار العلاجي; sexual relationship; Perception of disorder; Therapeutic course